Human Resources Accounting as Human Capital at PT. PAL Indonesia (Persero) - Harini, Riska Indah Suci; Raharjo, Ikhsan Budi; Priyadi, Maswar Patuh (Jurnal Akuntansi AKUNESA, 2025)
The purpose of this study was to determine: The process of decision making in human resource development at PT. PAL Indonesia (Persero); and The accounting treatment and disclosure of costs incurred in investing in human resource development at PT. PAL Indonesia (Persero). This research is a naturalistic study using a qualitative approach using interview and documentation techniques. The result of this research is the most valuable asset for PT. PAL Indonesia (Persero) is its human resources. PT. PAL Indonesia (Persero) provides training and development programs for its employees as an investment in human resources which will be the key in winning business competition. The accounting treatment and disclosure for investing in human resources are recognized as intangible assets in the financial statements, measured at cost and depreciated 4 years. PT. PAL Indonesia (Persero) has implemented PSAK 19: Intangible Assets in the recognition and disclosure of human resource investments.